140 Killed in Action (KIA): an analysis of military personnel who died of their injuries before reaching a definitive medical treatment facility in Afghanistan (2004–2014). Issue 12 (23rd November 2020) - Webster, Stacey; Barnard, Ed; Smith, Jason; Marsden, Max; Wright, Chris
Abstract : Aims/Objectives/Background: Most fatalities from trauma, in civilian and military settings, die before reaching a hospital. However, no previous studies have comprehensively examined this phase of care. The aim of this study was to define the time interval between injury and death in UK military personnel who died pre-hospital from enemy action (Killed in Action, KIA). Methods/Design: The UK Joint Trauma Theatre Registry (JTTR) was used to identify all UK military personnel who died in Afghanistan (2004–2014). Through novel linkage of medical and tactical databases, an accurate timeline of events was obtained. Cause of death was determined from post mortem review. The primary objective was to report time between injury and death. Secondary objectives: mortality at key timepoints, the temporal lethality of different anatomical injuries, and trends in the case fatality rate (CFR, defined as deaths/injuries x100). Data are reported as n(%), and median [inter-quartile range]. Proportions compared with a Fisher's exact test, and survival was with a Gehan-Breslow-Wilcoxon test; level of significance was corrected by Bonferroni. Results/Conclusions: 2413 UK personnel were injured in Afghanistan from 2004–2014; 448 died, a CFR of 18.6%. 390 (87.1%) of total deaths (KIA + Killed Non-Enemy Action) were prehospital. Complete timeline data were available for n =303 (87.1%) KIA – this cohort had a median injury severity score of 75.0 [55.5–75.0]. The median time between injury and death in KIA was 0.0 [0.0–21.8] minutes; 173 (57.1%) died immediately, and by 10 min more than two-thirds had died. Primary injury to the head had a significantly shorter time to death compared to the abdomen and lower extremity (both p <0.01). Significant improvement in survival over the decade was due to a reduction in pre-hospital CFR without an increase in in-hospital CFR. Over two-thirds of KIA deaths occurred within 10 min of injury. Improvement in the CFR in Afghanistan was predominantly in the prehospital phase.